Netralisasi Pada Pengolahan Limbah - Rochmi Widjajanti (Balai Besar Kimia dan Kemasan, 1995)
Naural ization is a part of Industrial waste water treatment. lnorder to help industrialists, many kinds of neutralization process and a simple way to find the neutralization chemi cals consumption are introduced.